GRATIS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The declaration that the 1980s were to be the Industrial Development Decade for Africa deepened awareness among individual African countries of the need for scientific and technological development: Ghana was no exception. In August 1980, the...